Nutrition facts and antioxidant activity of spices biscuits as functional snacks to immune booster - Nunung Cipta Dainy; Wilda Yunieswati (AcTion: Aceh Nutrition Journal, 2023)
The decline in the number of COVID-19 does not return people's conditions to the period before the pandemic. Efforts to prevent the spread of the coronavirus are still being carried out by implementing health protocols and keeping the body's immunity in top shape, one of which is by consuming balanced nutritious foods high in antioxidants. The research aims to develop high-antioxidant biscuits made from local flour and spices as a functional snack to increase the body's immune system. The research was held from September 2021 until January 2022 at the Faculty of Medicine and Health Universitas Muhammadiyah Jakarta. The research design was experimental, using a Completely Randomized Design (CRD). The biscuit formulation process was carried out by substituting wheat flour with purple sweet potato flour at five different ratios (4:0, 3:1, 2:2, 1:3, 0:4) and adding seven types of spices (Ginger, Cinnamon, Turmeric, Kencur, Lemongrass, Curcuma, and Cloves) with the same amount for each formula—a total of 30 semi-trained panelists in the sensory test. Data were analyzed using Kruskal Wallis. Proximate analysis and antioxidant analysis using the AOAC method and DPPH method. The results showed that the selected formula based on the sensory test was F2 with a ratio of wheat flour to purple sweet potato flour of 2:2. The hedonic test showed that there were significant differences in the color, texture, and aftertaste on biscuits (p=0,000, p=0,031, p=0,023 respectively). F2 is the formula the panelists chose, which has nutrition facts that meets SNI biscuits (2011) and has intense antioxidant activity (14,6 ug/mg).